Research on numerical model for flexural behaviors analysis of precast concrete segmental box girders. (15th September 2020) - Yan, Wu-Tong; Han, Bing; Xie, Hui-Bing; Li, Peng-Fei; Zhu, Li
Highlights: A fiber beam element with shear lag effects was proposed for box girders. A multi-node corotational slipping tendon element was proposed for unbonded tendon. The modeling approach of the joints between segments was suggested. A powerful tool for structural analysis of precast segmental girders was provided. Abstract: Precast concrete segmental girders (PCSGs) have recently become widely used construction technologies owing to their significant construction-related advantages. However, the segmental joints cause structural discontinuities, which generate more complicated mechanical behaviors than those observed with monolithic girders. Specifically, for PCSGs with external tendons, increasing attention is being paid to their structural analysis and design. In this paper, a new highly efficient numerical model is proposed for flexural behavior analysis of PCSGs over all the elastoplastic loading states. The proposed model is a beam-tendon element hybrid model comprising three components: the concrete box girder segment element, multi-node slipping tendon element and joint element. All of the elements are built considering the crucial mechanical behavior of PCSGs. A 10 degree-of-freedom (DOF) fiber beam element is proposed as the segment element to consider the shear lag effects, geometric and materially nonlinear behavior of the concrete box girder. A multi-node co-rotational slipping tendon element is proposed to model the slip effect and stiffness contribution of the un-bonded or external tendons. The discontinuous mechanical behavior between the segments is simulated using plain concrete joint elements with a modified constitutive relation based on the equivalent of the cracking and crushing energy. The finite element (FE) formulas and the modified method are deduced and presented in the paper and then implemented in OpenSees software as newly developed elements. Utilizing the developed procedure, the proposed model is thoroughly validated through comparisons with several scaled and full-scale experimental results, including structural deformations, ultimate capacity, traction increments of tendons and the width of the open joints. The results reveal the superior applicability and computational efficiency of the proposed model compared with previous models. Finally, the model is applied to a practice bridge for structural performance analysis under service and ultimate states. The applicability of the current design formulas is discussed based on the analytical results of the proposed model.